Defective Interfering Influenza Virus RNAs: Time To Reevaluate Their Clinical Potential as Broad-Spectrum Antivirals? - Dimmock, Nigel J.; Easton, Andrew J. (Journal of virology, 2014)
Defective interfering (DI) RNAs are highly deleted forms of the infectious genome that are made by most families of RNA viruses. DI RNAs retain replication and packaging signals, are synthesized preferentially over infectious genomes, and are packaged as DI virus particles which can be transmitted to susceptible cells. Their ability to interfere with the replication of infectious virus in cell culture and their potential as antivirals in the clinic have long been known. However, until now, no realistic formulation has been described. In this review, we consider the early evidence of antiviral activity by DI viruses and, using the example of DI influenza A virus, outline developments that have led to the production of a cloned DI RNA that is highly active in preclinical studies not only against different subtypes of influenza A virus but also against heterologous respiratory viruses. These data suggest the timeliness of reassessing the potential of DI viruses as a novel class of antivirals that may have general applicability.